In-Depth Analysis of Patient Experiences Through Health Communication - Rohimakumullah, Muhammad Al Assad; Wisudawaty, Hanna; Abdurrahman, Muhammad Sufyan; Wahyuni, Haria Saputry; Quddus, Zayyin Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Communication in the health industry can influence patient satisfaction. Patient satisfaction is an essential factor that can stimulate changes in healthcare quality through temporary patient-centred policies that communicate patient engagement in treatment decisions. However, patient satisfaction is challenging to define broadly, and satisfaction surveys do not often represent patient expectations. Numerous hospital customer satisfaction studies do not guarantee the outcomes of customer satisfaction questionnaires that deeply examine patients' perspectives on their intended goals or objectives. This study will examine how patient communication experiences, particularly for inpatients and hospital services, might shape expectations through data gathering via interviews and focus group discussions. This research utilizes communication experiences as the object of this research and the perspective of hospitalized patients or their families as the subject. Data was collected through interviews and focus group discussions (FGDs) to acquire information directly from the experiences of patients or patient families in four public hospitals in West Java Province with levels B and A. This study employs a qualitative analysis method that integrates a phenomenological approach and theories, using the Press Geney Experiment Patient Experience Survey as an analysis tool. The study's findings demonstrate that providing patients with relevant information at the right moment can make them feel more at ease and optimistic about their treatment and build trust in healthcare facilities.